Mixotrophic Growth of Astaxanthin-Rich Alga Haematococcus pluvialis using Refined Crude Glycerol as Carbon Substrate: Batch and Fed-Batch Cultivations - DECHATIWONGSE, Pongsathorn; CHOORIT, Wanna (Walailak Journal of Science and Technology (WJST), 2021)
Due to a current overabundance of crude glycerol produced from the biodiesel industry, the compound has the potential to be used as an inexpensive carbon source for growing the green microalga Haematococcus pluvialis (H. pluvialis), the richest source of natural astaxanthin (ATX). In order to investigate the practical use of crude glycerol, microalgal cultures were grown mixotrophically and heterotrophically in BG11 medium with the supplementation of refined crude glycerol, a mixture of glycerol and ethanol, under 2, 5 and 7 g L-1, using photoautotrophic cultivation as a control. H. pluvialis green-stage growth and red-stage ATX accumulation were effectively facilitated by mixotrophic conditions, with the highest µ of 0.27 ± 0.03 day-1 and the highest ATX content of (3.5 ± 0.4 % wt) (both observed under 7 g glycerol L-1). In contrast, growth was completely inhibited under heterotrophic conditions. Under repeated fed-batch operation, the exponential growth phase, during green-stage mixotrophic cultivation, was significantly extended from 5 days (in batch) to 24 days, making biomass yield of 1.86 ± 0.06 g DCW L-1 (around 2.6-fold higher). Monitoring of substrates (glycerol, ethanol and nitrate) in the broth was carried out and subsequently suggested that further optimization of media could be made.